Surgical Reconstruction of the Urinary Sphincter after Traumatic Longitudinal Disruption. (2nd September 2014) - Rehder, Peter; Schillfahrt, Florian; Skradski, Viktor
Abstract : The question is whether the urethral sphincter may be reconstructed after longitudinal injury similar to anal sphincter injuries. Analogue to obstetric, anal sphincter repair, an approximation repair of the sphincter may be feasible. An overlap repair is possible in anal sphincter repair, but because of the little tissue available in the urethral sphincter this is not an option. We describe three cases of urethral sphincter injury of different aetiologies. All resulted in a total longitudinal disruption of the muscular components of the urethral sphincter complex. After making the diagnosis of urethral sphincter injury, a primary approximation repair was done. Follow-up of at least two and up to three years is promising with one male patient being completely continent and the two female patients needing one safety pad per day. Longitudinal disruption of the muscular elements of the sphincteric urethra may be primarily reconstructed with good success using an approximation technique with simple interrupted sutures.